2019
DOI: 10.1039/c9ra03668g
|View full text |Cite
|
Sign up to set email alerts
|

Model Affitin and PEG modifications onto siRNA lipid nanocapsules: cell uptake and in vivo biodistribution improvements

Abstract: Surface modifications of siRNA LNCs were assessed with innovative TE-PEG polymers and an Affitin model, in comparison to classic DSPE-PEG LNCs, in order to evaluate the potential tumor targeting of siRNA after intravenous administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…The Benvegnu group has also worked extensively in the area of synthetic BA archaeasomes (Benvegnu et al, 2005 ; Jiblaoui et al, 2016 ; Resnier et al, 2019 ). In 2016 (Jiblaoui et al, 2016 ), they reported the synthesis and characterization of folate-conjugated archaeosomes (see Figure 5 ).…”
Section: Bolaamphiphile Specific Considerations Relevant To Biomedicamentioning
confidence: 99%
“…The Benvegnu group has also worked extensively in the area of synthetic BA archaeasomes (Benvegnu et al, 2005 ; Jiblaoui et al, 2016 ; Resnier et al, 2019 ). In 2016 (Jiblaoui et al, 2016 ), they reported the synthesis and characterization of folate-conjugated archaeosomes (see Figure 5 ).…”
Section: Bolaamphiphile Specific Considerations Relevant To Biomedicamentioning
confidence: 99%
“…Our data suggest that, due to our formulation strategy, pH-sensitive nanovectors would be able to reverse MDR phenotype to improve cancer treatment. Furthermore, as previously studied by our group [57,[63][64][65], different post-insertion strategies applied to LNC offer prospects for obtaining conclusive results about the effective ability of these nanoparticles to be loaded with the substances of interest, such as DNA, RNA or other drugs as ferrocifens.…”
Section: Discussionmentioning
confidence: 93%
“…2 ). A number of studies focusing on the engineering of nanoparticles for targeted delivery based on repebodies [ 49 , 50 , 51 ], affimers [ 52 ], affitins [ 53 , 54 , 55 ], and knottins [ 56 ] have also been conducted.…”
Section: The Main Structural Characteristics Of Scaffold Proteins And...mentioning
confidence: 99%